Dim artificial light at night alters immediate early gene expression throughout the avian brain - Hui, Cassandra K.; Chen, Nadya; Chakraborty, Arunima; Alaasam, Valentina; Pieraut, Simon; Ouyang, Jenny Q. (Frontiers in Neuroscience, 2023)
Artificial light at night (ALAN) is a pervasive pollutant that alters physiology and behavior. However, the underlying mechanisms triggering these alterations are unknown, as previous work shows that dim levels of ALAN may have a masking effect, bypassing the central clock. Light stimulates neuronal activity in numerous brain regions which could in turn activate downstream effectors regulating physiological response. In the present study, taking advantage of immediate early gene (IEG) expression as a proxy for neuronal activity, we determined the brain regions activated in response to ALAN. We exposed zebra finches to dim ALAN (1.5 lux) and analyzed 24 regions throughout the brain. We found that the overall expression of two different IEGs, cFos and ZENK, in birds exposed to ALAN were significantly different from birds inactive at night. Additionally, we found that ALAN-exposed birds had significantly different IEG expression from birds inactive at night and active during the day in several brain areas associated with vision, movement, learning and memory, pain processing, and hormone regulation. These results give insight into the mechanistic pathways responding to ALAN that underlie downstream, well-documented behavioral and physiological changes.